“Who Would Sexually Assault an 80-Year-Old Woman?”: Barriers to Exploring and Exposing Sexual Assault Against Women in Late Life - Goldblatt, Hadass (Journal of interpersonal violence, 2022)
The phenomenon of Sexual Assault against Women in Late Life (SAWLL) has received increasing research attention in recent years. Yet, there is still only scant knowledge on it, compared with research on the sexual assault of younger women. Sexual assault is considered a sensitive topic, generally characterized by a conspiracy of silence. The aim of this article is to explore the barriers that hinder the identification and exposure of SAWLL, as reported by professionals. The research question was as follows: How do welfare and health care professionals present the motives and processes that obstruct exploring, exposing, and intervening in cases of SAWLL? A qualitative research design was used. Participants were 18 experienced welfare and health care professionals engaged in intervention with sexual assault in late life victims as well as offenders. Data were collected through in-depth, semi-structured interviews, which were later transcribed and thematically analyzed. Four themes emerged from the data analysis: (a) Leading Negative Emotions, (b) Lack of Language, (c) Implications of Cumulative and Complex Trauma, and (d) Social Exclusion. Women and professionals alike undergo complementary processes involving silence and silencing. These processes construct a “wall” of barriers, requiring professionals’ sensitivity and awareness to deconstruct these barriers. Professional intervention through open discourse with the abused women can break this conspiracy of silence. We recommend that training programs for professionals intervening in cases of elder abuse and neglect will be directed along two paths: The first path should focus on professionals’ competence and skills, and the second path should address the women’s specific needs. These programs will include a particular module that will specifically address SAWLL. This module should comprise knowledge on typical emotional reactions to SAWLL, the use of language in creating reality, cumulative and complex trauma, and the social construction of ageism and sexism, which lead to social exclusion.